A Model of Short-Run Bank Behavior - Aigner, Dennis J.; Bryan, William R. (Quarterly Journal of Economics, 1971)
I. Recent literature, 97.—II. The business of banking and the adjustment gap, 99.—III. The model, 101.—IV. Empirical results, 109.—V. Conclusions, 117.